Clinical diagnosis, treatment and prognosis analysis of children with pancreatic tumours - Zhang, Yao; Yang, Chao; Zhao, Zhenzhen (Frontiers in Pediatrics, 2025)
ObjectiveTo investigate the diagnosis, treatment, and prognosis of children with pancreatic tumours.MethodsWe conducted a retrospective review of patients ≤18 years of age with pancreatic neoplasms who underwent surgery at a single institution between 2010 and 2022.ResultsThe most common histology among the 48 patients was solid pseudopapillary neoplasm of the pancreas (SPN, n = 32), followed by pancreatic blastoma (PB, n = 12), B-cell lymphoblastic lymphoma (n = 1), leukaemia (n = 1), pancreatic cancer (n = 1), and pancreatic neuroendocrine tumours (n = 1). The tumours were located in the head of the pancreas in 29 patients (10 patients underwent pancreaticoduodenectomy, 9 patients underwent Whipple, 7 patients underwent pancreatic tumour resection, and 3 patients underwent laparoscopic tumour enucleation). The tumours were located in the tail of the pancreatic body in 19 patients (10 patients underwent local resection of the pancreatic tumour, 5 patients underwent resection of the pancreatic body and tail and spleen, 3 patients underwent spleen-preserving distal pancreatectomy, and 1 patient underwent laparoscopic resection of the tumour). Patients with pancreatoblastoma, acute lymphoblastic leukaemia, B lymphoblastic lymphoma or pancreatic cancer were treated with regular chemotherapy. Forty-five patients (93.75%) were currently alive and disease free, and the median follow-up was 8.2 years (IQR: 2.0–14.3). Two patients with pancreatic blastoma died during the follow-up, and 1 patient with pancreatic cancer died due to tumour recurrence and progression after treatment.ConclusionPaediatric pancreatic tumours are highly heterogeneous. Complete surgical resection that preserves organ function is the preferred treatment for children with pancreatic tumours.